Genomic landscape of nosocomial Acinetobacter baumannii: A comprehensive analysis of the resistome, virulome, and mobilome - Sara Pearl; Anand Anbarasu (Scientific Reports)
Abstract Acinetobacter baumannii (A. baumannii) is a major multidrug-resistant pathogen, posing serious threats in the healthcare settings. This study provides a comprehensive genomic analysis of nosocomial A. baumannii whole-genome sequences retrieved from NCBI Genome database. Multilocus sequence typing and capsule typing were performed to investigate the clonal diversity. The genomes were characterized to identify antimicrobial resistance genes (ARGs), virulence factors, and mobile genetic elements. Further, pangenome analysis was conducted to examine the core and accessory genomes of A. baumannii. Our dataset comprised of 609 genomes deposited from diverse geographic regions worldwide between 2004 and 2024. The genomes showed high clonal heterogeneity, with sequence type ST2 being the predominant sequence type. A total of 185 unique ARGs were identified, with majority of them associated with efflux pump and β-lactamase coding genes. Over 25,000 IS elements were detected, with IS4 family being the prevalent type. High abundance of integron-mediated resistance determinants, especially for aminoglycosides and β-lactams, were identified. The open pangenome window due to its larger accessory genome suggested substantial genome plasticity. Our findings highlight A. baumannii’s rapid evolution and resistance potential, emphasizing need for alternative therapeutic strategies. Enhanced surveillance, infection control measures, and antimicrobial stewardship are crucial to combat this persistent threat.